Aging impairs contraction-induced human skeletal muscle mTORC1 signaling and protein synthesis - Fry, Christopher S; Drummond, Micah J; Glynn, Erin L; Dickinson, Jared M; Gundermann, David M; Timmerman, Kyle L; Walker, Dillon K; Dhanani, Shaheen; Volpi, Elena; Rasmussen, Blake B (Skeletal muscle, 2011)
Sarcopenia, the loss of skeletal muscle mass during aging, increases the risk for falls and dependency. Resistance exercise (RE) training is an effective treatment to improve muscle mass and strength in older adults, but aging is associated with a smaller amount of training-induced hypertrophy. This may be due in part to an inability to stimulate muscle-protein synthesis (MPS) after an acute bout of RE. We hypothesized that older adults would have impaired mammalian target of rapamycin complex (mTORC)1 signaling and MPS response compared with young adults after acute RE. We measured intracellular signaling and MPS in 16 older (mean 70 ± 2 years) and 16 younger (27 ± 2 years) subjects. Muscle biopsies were sampled at baseline and at 3, 6 and 24 hr after exercise. Phosphorylation of regulatory signaling proteins and MPS were determined on successive muscle biopsies by immunoblotting and stable isotopic tracer techniques, respectively. Increased phosphorylation was seen only in the younger group (P< 0.05) for several key signaling proteins after exercise, including mammalian target of rapamycin (mTOR), ribosomal S6 kinase (S6K)1, eukaryotic initiation factor 4E-binding protein (4E-BP)1 and extracellular signal-regulated kinase (ERK)1/2, with no changes seen in the older group (P >0.05). After exercise, MPS increased from baseline only in the younger group (P< 0.05), with MPS being significantly greater than that in the older group (P <0.05). We conclude that aging impairs contraction-induced human skeletal muscle mTORC1 signaling and protein synthesis. These age-related differences may contribute to the blunted hypertrophic response seen after resistance-exercise training in older adults, and highlight the mTORC1 pathway as a key therapeutic target to prevent sarcopenia.